BULLYING BEHAVIOR AND HUMAN HEALTH: FACTORS AND CAUSES - Bakhtawar Siddique; Dr Waleed Khan; Dr Umara Rauf (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Bullying behavior is a complex phenomenon influenced by various factors such as biological, environment, psychological, social dynamics, and situational circumstances. Understanding these causes is crucial for effectively managing and preventing bullying behavior. By identifying the root causes, targeted interventions can be developed to address specific factors and provide support to individuals exhibiting bullying behaviors. It’s important to adopt a holistic approach that considers multiple factors, including the individual’s biological, environmental, psychological, and social conditions. Bullying can have profound and lasting effects on children, impacting their emotional well-being, cognitive functioning, behavior, and social development. Children who experience bullying may face fear, anxiety, low self-esteem, academic difficulties, and struggles in building healthy relationships. Some may internalize their anxiety and withdraw, while others may externalize their emotions through self-bullying or engage in self-destructive behaviors. Socially, bullying can hinder a child’s ability to form trusting relationships and interact with peers, leading to distorted beliefs about trust and conflict resolution. Recognizing the impact of bullying is crucial for implementing early interventions, counseling, and creating safe environments to help affected children heal and recover. By addressing the emotional, cognitive, behavioral, and social consequences of bullying, the long-term effects on children’s well-being and development can be reduced.